Diagnosis and Management of Hair Loss in Pediatric - Fitriani, Fitriani; Antonius, Cayadi Sidarta; Kartowigno, Soenarto; Diba, Sarah; Argentina, Fifa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Hair loss can occur in pediatric and adult populations and may have different patterns. The causes of hair loss in pediatric patients include tinea capitis, alopecia areata, telogen effluvium, traction alopecia, anagen effluvium, androgenetic alopecia, loose anagen syndrome, short anagen syndrome, congenital aplasia cutis, congenital triangular alopecia, atrichia congenita, congenital hypotrichosis, and transient neonatal hair loss.Purpose: to understand etiologies of hair loss in pediatrics, and to determine the appropriate examinations for diagnosing and managing hair loss in children.Review: Hair loss in children can be categorized as congenital or acquired. Congenital hair loss is classified based on distribution, while acquired hair loss is classified as either scarring or non-scarring. Hair loss complications in children can be irreversible. The diagnosis of hair loss in pediatric patients includes anamnesis, physical examination, and supporting examinations. The supporting examinations used for diagnosis include fungal cultures, hair pull tests, hair tug tests, light microscopy, and trichoscopy. Conclusion: There are numerous causes of hair loss in pediatric patients that need to be identified before appropriate management can be implemented. The management of hair loss requires a holistic approach, including psychosocial support. Correct diagnosis and treatment of pediatric hair loss can prevent a decrease in the patient's quality of life.